Selection evaluation of in-situ exploitation of oil shale in Sinopec exploration areas and adjacent areas - GUO Xusheng, LI Wangpeng, SHEN Baojian, HU Zongquan, ZHAO Peirong, LI Maowen, GAO Bo, FENG Dongjun, LIU Yali, WU Xiaoling, SU Jianzheng (Youqicang pingjia yu kaifa)
Oil shale in the Sinopec exploration areas is abundant and serves as an important strategic reserve and supplementary energy source for the country. Accelerating the exploration and development of oil shale is crucial for improving China’s energy structure and ensuring national energy security. To achieve large-scale exploration and cost-effective development of oil shale, the technologies of in-situ exploitation field tests successfully conducted both domestically and internationally were reviewed and summarized. Based on this review, the characteristics of test areas, geological and engineering adaptability, and selection layer requirements were analyzed. It was concluded that field pilot tests of Shell’s electric heating method, Jilin Zhongcheng Company’s in-situ fracturing chemical retorting technology, and Jilin University’s local chemical reaction-based in-situ pyrolysis technology have been successfully carried out. However, the maturity and feasibility of two technologies in China need to be further studied and validated, and the adaptability of existing in-situ exploitation technologies to deep oil shale remains unverified. The technical characteristics, geological resource conditions, and exploitation engineering conditions of in-situ oil shale exploitation were reviewed and analyzed. Based on the key factors restricting in-situ exploitation of oil shale in China and the heating method, four geological parameters, six engineering parameters, and classification evaluation limits were determined. Additionally, the weights of each parameter were assigned according to the degree of constraints on in-situ exploitation and utilization of oil shale. A two-factor evaluation model of geological and engineering for identifying favorable areas for in-situ oil shale exploitation was then established, leading to the selection of 15 Class Ⅰ favorable areas in Sinopec exploration areas and adjacent areas. The effects of key factors, including roof and floor, fractures, and movable water, on the selected favorable areas were further analyzed. Through comprehensive evaluation, four target areas were selected: the Xunyi mining area on the southern margin of the Ordos Basin, the Shanghuangshan Street mining area on the southern edge of the northern piedmont of the Bogda Mountains, the Dianbai mining area in the Maoming Basin, and the Fushun mining area in the Fushun Basin.